Heterogeneity of regional systolic function detected by tissue Doppler imaging is linked to impaired global left ventricular relaxation in hypertrophic cardiomyopathy. Issue 10 (15th January 2008) - Kato, T S; Izawa, H; Komamura, K; Noda, A; Asano, H; Nagata, K; Hashimoto, S; Oda, N; Kamiya, C; Kanzaki, H; Hashimura, K; Ueda, H I; et al.
Abstract : Objective: To evaluate regional and global left ventricular (LV) function and LV wall thickness (LVWT) in patients with hypertrophic cardiomyopathy (HCM). Design and setting: Observational study at the National Cardiovascular Centre and Nagoya University Hospital in Japan. Participants: Thirty-six patients with HCM and 16 patients with hypertensive LV hypertrophy (LVH). Main outcome measures: Conventional echocardiography and strain rate (SR) imaging derived from tissue Doppler imaging were performed. Systolic strain (ϵsys ), peak systolic SR (SRsys ), peak early diastolic SR (SRdia ) and LVWT were obtained from eight LV segments. LV pressure was simultaneously recorded with a high-fidelity micromanometer. Results: The regional ϵsys and SRsys were correlated with LVWT in patients with HCM ( r  = 0.50, p<0.001 and r  = 0.63, p<0.001, respectively) but not in patients with hypertensive LVH. The standard deviations of LVWT, ϵsys and SRsys obtained from the eight LV segments of each subject were greater for patients with HCM than for patients with hypertensive LVH. The standard deviation of LVWT was correlated with those of ϵsys and SRsys ( r  = 0.55, p<0.001 and r  = 0.56, p<0.001, respectively). The standard deviations of LVWT, ϵsys and SRsys were correlated with tau ( r  = 0.35, p<0.05; r  = 0.47, p<0.001; and r  = 0.39, p<0.005, respectively). Conclusions: Heterogeneity of regional LV systolic function detected by SR imaging is in part attributable to heterogeneity of LVH and may be linked to impaired global LV relaxation in HCM.